Stabilization of Peat Soil by Using Effective Microorganism (EM) - Samsuddin, Nur Syasalbila Peat soil is one of the most soft soils ever exis (IRC, 2016)
Peat soil is one of the most soft soils ever exist around the world and classified as highly organic. Peat are well known for their high compressibility, natural moisture content, low shear strength and long term settlement. The aim of this study is to obtain the stabilized peat soils by using the Effective Microorganisms (EM). The volume of EM added and mixed with peat soils varied with 2%, 4%, 6%, 8% and 10% and then were cured for 7, 14 and 21 days after being compacted in the PVC mould with 5 blows for each layer for 3 layers. The experiment was done for uncontrolled and controlled moisture content which means that the uncontrolled moisture content does not have specific moisture content for the samples compared to controlled moisture content that have 50% of moisture content.